Industrial-scale purging of ammonia by using nitrogen before environmental discharge - Gezerman, Ahmet Ozan (SPRINGER HEIDELBERG, 2016)
For efficient discharge and storage of refrigerated chemicals such as ammonia, special processes must be developed, and several related parameters must be checked and evaluated. In this study, pressure changes in ammonia storage systems that are purged by nitrogen gas, during filling by gaseous ammonia, were calculated and an environment-friendly technique for discharging ammonia gas was developed. In addition, exergy analysis for the system was performed, and the nitrogen discharge rate in the system was calculated. The total exergy loss was determined to be 43.18 %, and the nitrogen discharge rate was determined to be 38,995 dm(3) h(-1) for the proposed system.
Keywords: Purging; Ammonia; Nitrogen; Cryogenic; Multistage compressor; Chemistry